Recent occurrence of large jokulhlaups at Lake Tuborg, Ellesmere Island, Nunavut - Lewis, Ted; Francus, Pierre; Bradley, Raymond S. (Journal of Paleolimnology, 2009)
The varved sediment record from glacially-fed Lake Tuborg, Ellesmere Island, Nunavut, shows that only three large jokulhlaups have occurred there in the last millennium: 2003, 1993, and 1960. Detailed analyses of sediment microstructure and particle size, combined with in-situ hydrometeorological and limnological process studies, allowed jokulhlaup facies identification and discrimination from deposits from other processes. Deposits from large jokulhlaups are anomalously thick, typically lack internal structure, have sharp bases, and fine upwards. The ice-dammed lake above Lake Tuborg (the source of the jokulhlaups) likely changed its drainage style in 1960, from ice-dam overtopping to ice-dam flotation and glacial tunnel enlargement by melt widening, which allowed the lake to drain completely and catastrophically. Complete drainage of ice-dammed lakes by ice-dam flotation is rare in the region is due to the pervasiveness of cold-based ice. Twentieth century warming is likely responsible for some combination of dam thinning, lake expansion and deepening, and changing the thermal regime at the base of the dam. Anomalously thick individual varves were periodically deposited beginning in the nineteenth century, and their thickness increased with time. This likely reflects a combination of increased ice dam overtopping, subaqueous slope failures, sediment availability and rising air temperature. The varve record presented here significantly correlates with a previous, shorter record from Lake Tuborg. However, generally weak correlations are found between the new varve time series, regional records of air temperature, and glacial melt from ice cores on the Agassiz Ice Cap. It is hypothesized that on short timescales, sedimentation at the coring location reflects a complex and varying integration of multiple hydroclimatic, geomorphic and limnologic influences.
id: 1998; PT: J; UT: WOS:000263543300006